2017
DOI: 10.1038/ncomms14626
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controlled terahertz magneto-optical phenomena in continuous and patterned graphene

Abstract: The magnetic circular dichroism and the Faraday rotation are the fundamental phenomena of great practical importance arising from the breaking of the time reversal symmetry by a magnetic field. In most materials, the strength and the sign of these effects can be only controlled by the field value and its orientation. Furthermore, the terahertz range is lacking materials having the ability to affect the polarization state of the light in a non-reciprocal manner. Here we demonstrate, using broadband terahertz ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 49 publications
2
57
2
Order By: Relevance
“…2(a), and a Fermi level E F ¼ 0.2 eV (equivalent, at B ¼ 0, to a carrier density n ≈ 3 × 10 12 cm −2 ). Antidot lattices like these are well within experimental capabilities [56][57][58][59][60]. The eigenvalue problem, Eqs.…”
mentioning
confidence: 99%
“…2(a), and a Fermi level E F ¼ 0.2 eV (equivalent, at B ¼ 0, to a carrier density n ≈ 3 × 10 12 cm −2 ). Antidot lattices like these are well within experimental capabilities [56][57][58][59][60]. The eigenvalue problem, Eqs.…”
mentioning
confidence: 99%
“…Due to their ease of manipulation, metasurfaces, the two-dimensional analogues of metamaterials, offer the most promising playground to realize dynamical effects [1,28,29], also due to the rise of tunable twodimensional materials [30,31]. Recently, graphene has emerged as a platform to enhance light-matter interactions [32][33][34][35], realizing atomically thin metasurfaces [12,[36][37][38][39]. Its doping level, which can be as high as ≈ 2 eV [40,41], can be dynamically modulated, with reported response times of ≈ 2.2 ps, and relative modulations of 38% [42].…”
mentioning
confidence: 99%
“…Poumirol et al [138] demonstrated the electrical control of the magneto-optical properties of graphene. Electrostatic control of magnetic circular dichroism (MCD) and Faraday rotation (FR) was achieved in an atomically thin sheet of graphene.…”
Section: Electrically Tunable Magneto-optics In Graphenementioning
confidence: 99%